Penyimpangan dan Masalah Sosial dalam Olahraga: Implikasi terhadap Sportivitas, Keadilan, dan Integritas Olahraga - Yan Indra Siregar; Putra Arima; Indrian Saputra Sitinjak; Duleva Berry Aritra Kaban; Muhammad Rizki Berutu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social deviance and social problems in sports have become increasingly complex along with the development of modern sports. Various issues such as violence in sports, doping, gender discrimination, unfair competition, and declining sportsmanship can negatively affect the integrity and educational values of sports. This study aims to analyse the forms, causes, impacts, and prevention efforts related to social deviance and social problems in sports. The research employed a Systematic Literature Review (SLR) method by examining scientific articles and relevant references published between 2021 and 2026. Data were collected through the processes of identification, selection, evaluation, and synthesis of literature related to sports sociology and social issues in sports. The results indicate that social deviance in sports is influenced by individual, social, cultural, and organizational factors. The most frequently reported forms of deviance include violence, doping, and gender discrimination. These problems contribute to the decline of sportsmanship, public trust, fairness, and the integrity of sporting competitions. Furthermore, the findings reveal that preventive efforts can be implemented through strengthening regulations, ethical education, character development, and the promotion of fair play values. In conclusion, collaboration among athletes, coaches, sports organizations, educational institutions, and society is essential to minimize social deviance and promote a healthy sporting environment.